A Novel Secure Arithmetic Image Coding Algorithm Based on Two-Dimensional Generalized Logistic Mapping - Liu Huiying; Xu Caiyun; Kong Jun; Du Ying (2015 Fifth International Conference on Instrumentation and Measurement, Computer, Communication and Control (IMCCC), 2015)
A novel secure arithmetic image coding algorithm based on Two-dimensional Generalized Logistic Mapping is proposed. Firstly, according to the digital image size m×n, two 2D chaotic sequences are generated by logistic chaotic mapping. Then, the original image data is scrambled by sorting the chaotic sequence. Secondly, the chaotic sequence is optimized to generate key stream which is used to mask the image data. Finally, to generate the final output, the coding interval order is controlled by the chaotic sequence during the arithmetic coding process. Experiment results show the proposed secure algorithm has good robustness and can be applied in the arithmetic coder for multimedia such as video and audio with little loss of coding efficiency.